QUALITY ANALYSIS AND CHARACTER ASSOCIATION STUDIES OF RICE UNDER SRI BASED CULTIVATION PRACTICES - DAMINI THAWAIT; SANJAY; K. DWIVEDI,; AMIT KUMAR PATEL; ,SRISHTI PANDEY; MANISH KUMAR SHARMA (The Bioscan, 2015)
The present investigation is carried out to study the correlation and path analysis in scented long duration variety of rice (Oryza sativa L.). Character association of the yield attributing traits revealed significantly positive association of grain yield exhibited significant positive correlation with root dry weight (0.657), number of tillers hill-1 (0.636), test weight (0.601), panicle length (0.594), panicle weight (0.537) and dry weight (0.535). Hence, selection for the traits can improve yield. Whereas in quality analysis the highest length breadth ratio (3.29) found in treatment having 20cm x 20cm spacing with two seedlings per hill. Based on the result of the study, the treatment with spacing 25 cm from row to row and 25 cm from plant to plant with two seedlings per hill, have good cooking and eating quality, hence selection for improvement based on these parameters will be a right step in the right direction for obtaining good quality grains.